DIAGNÓSTICO E EVOLUÇÃO DO SETOR DE SERVIÇOS NAS REGIÕES FRONTEIRA NOROESTE E NOROESTE COLONIAL DO RIO GRANDE DO SUL - Jasiowka, Dieny P. V.; Zamberlan, Luciano; Kuhn, Ivo N.; Soares, Julio C. V.; Froemming, Lurdes M. (Salão do Conhecimento, 2013)
Resumo